Impacts of industrial agglomeration on industrial pollutant emissions: Evidence found in the Lanzhou–Xining urban agglomeration in western China - Jia, Zhuo; Chen, Qi; Na, Heya; Yang, Yongchun; Zhao, Jinyao (Frontiers in Public Health, 2023)
While industrialization has promoted China's rapid economic growth, it has also led to an increase in industrial pollutant emissions. The increase in industrial pollutant emissions from China's industrialization not only affects public health but also affects the sustainable development of the economy and society. The pollution generated from China's industrial production is more serious than that which is generated in daily life, and preventing and controlling the discharge of industrial pollution have become an important goals of environmental pollution control in China. The Lanzhou–Xining urban agglomeration is an important carrier for economic development and industrial agglomeration, located in the upper reaches of western China. It comprises 41 counties in Lanzhou, Xining, Baiyin, Dingxi, Linxia, and Haidong. Lanzhou–Xining has the typical characteristics of a western China urban agglomeration: 1) pollution-intensive industries account for a high proportion of the regional industrial structure; 2) industrial pollutant emissions account for a high proportion of the total regional pollutant emissions. 3) contradiction between industrial development and industrial pollution prevention is prominent. The Lanzhou–Xining urban agglomeration has absolute advantages in the support of pollution-intensive industries, such as the presence of a petrochemical industry, non-ferrous metallurgy, salt chemical industry, building materials and energy supply. Thus, the environmental pressure brought on by pollution-intensive industries is increasingly severe. Based on data from 41 counties of the Lanzhou–Xining urban agglomeration in western China from 2010 to 2018, this study uses spatial analysis to reveal the spatial characteristics of industrial agglomeration and industrial pollutant emissions. Spatial factors are introduced into the classic STIRPAT model, and a spatial economic model is constructed to analyze the impact of industrial agglomeration, population density, economic level, technological level, industrial structure, and other factors on industrial pollutant emissions from a spatial perspective, investigating the impact of industrial agglomeration on industrial pollutant emissions in the Lanzhou–Xining urban agglomeration of western China.